Pemenuhan Kebutuhan Spiritual untuk Menurunkan Tingkat Stress pada Narapidana Perempuan - Lia Kurniasari; Lely Mustikarani; Ghozali Ghozali (Faletehan Health Journal, 2021)
Stress is a condition caused by thoughts, emotions and spirituals and ranked 4th in the world. Experiencing stress needs spiritual power to help one’s healing. Having a good spiritual can help individuals to be more patient, calmer, more peaceful and more sincere in dealing with problems. The purpose of this study was to determine the correlation between spiritual needs fulfillment and prisoners’ stress level at Class IIA Women’s Prisons in Samarinda. The method used a cross sectional research design and simple random sampling with the sample size of 180 people. The research instrument was a questionnaire and the bivariate analysis used chi square. The results showed that the prisoners’ spiritual needs were met and their stress levels were normal. The analysis results showed that there was a significant relationship between the spiritual needs fulfillment the stress level of prisoners at Class IIA Women's Prison in Samarinda (pv = 0.026).